Old baggage : a novel - Evans, Lissa (Harper Perennial, 2019)
"1928. Riffling through a cupboard, Matilda Simpkin comes across a small wooden club--an old possession that she hasn't seen for more than a decade. Immediately, memories come flooding back to Mattie--memories of a thrilling past, which only further serve to remind her of her chafingly uneventful present. During the Women's Suffrage Campaign, she was a militant who was jailed five times and never missed an opportunity to return to the fray. Now in middle age, the closest she gets to the excitement of her old life is the occasional lecture on the legacy of the militant movement. After running into an old suffragette comrade who has committed herself to the wave of Fascism, Mattie realizes there is a new cause she needs to fight for and turns her focus to a new generation of women. Thus the Amazons are formed, a group created to give girls a place to not only exercise their bodies but their minds, and ignite in young women a much-needed interest in the world around them. But when a new girl joins the group, sending Mattie's past crashing into her present, every principle Mattie has ever stood for is threatened"--